DAMPAK SERTIFIKASI TERHADAP KOMPETENSI PEDAGODIK GURU (STUDI PEMETAAN (PK) GPAI ON-LINE TINGKAT SMA/SMK PROVINSI SUMATERA SELATAN - Muhammad Ali; Syarnubi Syarnubi (Tadrib: Jurnal Pendidikan Agama Islam, 2020)
Certification is one of the breakthroughs to improve teacher professionalism. This means that if the teacher's competence is good, then the performance will be good too. Certification should not be used as an arena for economic improvement, but the event to improve professional competence in teaching. So that certified teachers are professional teachers in educating students. The problem of this study is the impact of PAI SMA/SMK teacher certification on pedagogical competencies (study of PK Online values). Therefore this study aims to determine the impact of certification on the pedagogical of high school teachers in South Sumatra Propince, which includes Pedagogical 1 (learning painning), Pedagogical 2 (learning model), and Pedagogical 3 (learning assessment).This type of research is qualitative descriptive research. The subjects in this study were certified teachers in the city of Palembang and the data used through data documentation. From this study it can be concluded that the implementation of certification followed by certified teachers in the Province of South Sumatra under the auspices of the Ministry of Religion. Teachers who have been certified both civil servants and non-civil servants who have received the Ministry of Religion and Ministry of Education in the Province of South Sumatra are 1219 people. Teacher's performance before certification cannot be measured. After the PAI teacher competency mapping activities, the competency of PAI and Budi Pekerti teachers was seen in the Province of South Sumatra.